Gaseous molecules-mediated electrochemical exfoliation of halogenated MXenes and its boosting in wear-resisting tribovoltaic devices - Qi Fan; Minghua Chen; Longyi Li; Minghui Li; Chuanxiao Xiao; Tianci Zhao; Long Pan; Ningning Liang; Qing Huang; Lijing Yu; Laipan Zhu; Michael Naguib; et al. (Nature Communications)
Abstract Two-dimensional transition metal carbides and/or nitrides (MXenes), especially their few-layered nanosheets, have triggered burgeoning research attentions owing to their superiorities including extraordinary electrical conductivity, accessible active surface, and adjustable processability. Molten salts etching route further achieves their controllable surface chemistry. However, the method encounters challenges in achieving few-layered structures due to more complex delamination behaviors. Herein, we present an efficient strategy to fabricate Cl- or Br-terminated MXene nanoflakes with few-layers, achieved by electrochemical intercalation of Li ions and concomitant solvent molecules from the electrolyte solution, with gaseous propylene molecules to disrupt interlayer forces. By controlling cut-off voltages, the optimal protocol results in nanosheets with a recovery rate of ~93% and preserved surface chemistry. The resultant MXenes dispersions were employed as lubricants to enhance tribovoltaic nanogenerators, where Ti3C2Br2 displayed superior electrical output. These findings facilitate the understanding of MXenes’ intrinsic physical properties and enable the nanoengineering of advanced electronic devices.